Composition and diversity of rhizosphere microorganisms of Suaeda salsa in the Yellow River Delta - Xu, Hui; Li, Na; Li, Wenjuan; Wang, Hongguo; Shao, Yan; Liu, Jingmei; Zhang, Jiabo; Wang, Jun; Shang, Shuai (Frontiers in Ecology and Evolution, 2024)
Introduction: Suaeda salsa is a typical wetland plant species in coastal areas that plays an important role in protecting the marine eco-environment. The rhizosphere microorganisms of S. salsa are responsible for its growth and development.Method: Eighteen samples were collected from three areas, including the natural S. salsa-growing area (YDJ), artificial S. salsa restoration area (YDB), and nonrestoration area (BKS), and highthroughput sequencing technology was employed to explore the characteristics of the rhizosphere microorganisms of S. salsa in the Yellow River Delta.The results illustrated that the abundance and diversity of soil bacteria were highest in the YDJ group, fungal abundance was highest in the YDJ group, and fungal diversity was greatest in the YDB group. In total, 26,663 OTUs were found in soil bacteria, among which 9,095, 8,023, and 11,001 were detected in the BKS, YDB, and YDJ groups, respectively.11,619 OTUs were found in soil fungi, among which 4,278, 4,552, and 5,100 were detected in the BKS, YDB, and YDJ groups, respectively. The YDJ group had the highest number of operational taxonomy units (OTUs) for bacteria and fungi among the three groups.Discussion: S. salsa in natural wetland conditions tended to be similar to artificially restored S. salsa.The composition of fungi in the S. salsa rhizosphere had greater similarities than that of the bacteria.Proteobacteria had the highest abundance among bacterial communities, and Ascomycota, Basidiomycota, and Olpidiomycota were dominant in the fungal communities of the three groups.The correlation results found that power of hydrogen (pH) was significantly and negatively correlated with the abundance of Acidobacteriota and Proteobacteria. Meanwhile, electrical conductivity (EC) was significantly and positively correlated with the abundance of Firmicutes and negatively correlated with that of Proteobacteria. Regarding fungi, pH and EC were significantly and negatively correlated with the abundance of Chytridiomycota. Our findings provided some theoretical data for S. salsa conservation and wetland restoration.